Grocery Shopping in the UK: A study of consumers - Finlay, Louise (2007)
Over the last fifty years grocery shopping in the IK has been transformed by the rise of the supermarkets. The top four retailers in the sector control over 60% of the market. This dominance would not have been possible without the support of the consumer. Supermarkets deliver low prices and convenient one-stop shops offering the full range of grocery and other products. However there are increasing concerns that this revolution has gone too far. The competition Commission has recently referred supermarkets to the OFT for investigation of anti competitive practices. This is the third such study in the last decade. The dominance of the format may imply that consumers are no longer ably to exercise free choice when grocery shopping, as viable alternative outlets no longer exist. This study finds that whilst consumers have picked up on media concerns, the habitual nature and low cognitive processing characteristic of grocery purchases means that consumers are rarely prepared to change their shopping patterns to access alternative outlets. Supermarket power may have implications for the agricultural, economic and environmental health of the nation, but these issues are too remote from the consumer to force a change in behaviour.